Determinant Analysis Of Credit Distribution In Regional Development Bank In Indonesia - Agung Nur Prastiyo; Emanuel Kristijadi (MediaTrend, 2023)
This study uses the cross-section of time series data from 2011-2020 and Regional Development Banks in Indonesia. The method used in this study is the panel data regression method with the Fixed Effect GLS approach. Econometric analysis using panel data regression models to identify the variables that affect lending. This study aims to analyze the effect of Capital, Profitability, Bank Health, and Inefficiency on lending at Regional Development Banks. The analysis results show that simultaneously the independent variables significantly affect the dependent variable. Furthermore, partial Return On Assets positively and substantially affects lending at Regional Development Banks in Indonesia.